Hormonal contraceptive use and HIV-1 infection in a population-based cohort in Rakai, Uganda - Kiddugavu, Mohammed; Makumbi, Fred; Wawer, Maria J.; Serwadda, David; Sewankambo, Nelson K.; Wabwire-Mangen, Fred; Lutalo, Tom; Meehan, Mary; Gray, Ronald H. (Aids, 2003)
Hormonal contraceptives have been associated with increased risk of HIV acquisition. Methods: The association between hormonal contraception use and HIV acquisition was assessed in a rural community-based cohort in Rakai District, Uganda. A group of 5117 sexually active HIV-negative women were surveyed at 10 month intervals between 1994 and 1999. Information on demographic and sociobehavioral characteristics, use of hormonal contraception (pill and injectable methods), condoms and the number of sexual partners was obtained by home-based interview. HIV incidence rate ratios (IRR) and 95% confidence intervals (CI) associated with hormonal contraception were estimated by multivariate Poisson regression after adjustment for age, condom use, number of sexual partners, marital status, education and history of genital ulcer disease. Results: At one or more interviews, 16.6% of women reported use of hormonal contraceptives and 23.0% reported condom use. HIV incidence was 2.3/100 personyears in hormonal contraceptive users compared with 1.5/100 person-years in non-hormonal contraceptive users (unadjusted IRR, 1.56; 95% CI, 1.00–2.33). After multivariate adjustment, the IRR associated with hormonal contraceptives was reduced to 0.94 (95% CI, 0.53–1.64). The adjusted IRR was 1.12 (95% CI, 0.48–2.56) with oral contraceptive use and 0.84 (95%CI, 0.41–1.72) with injectable methods. Conclusion: Use of hormonal contraception is not associated with HIV acquisition after adjustment for behavioral confounding
Keywords: hormonal contraceptives; injectable; pills; DMPA; HIV; heterosexual transmission; risk factors; sexual behavior